2019
DOI: 10.1039/c9sm01607d
|View full text |Cite
|
Sign up to set email alerts
|

Self-regenerating compliance and lubrication of polyacrylamide hydrogels

Abstract: In this work, careful experiments reveal how abrasive wear of polyacrylamide hydrogels only temporarily alters the surface properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 58 publications
0
15
1
Order By: Relevance
“…By calculating the Hertzian contact diameters, 34 we could get the friction state. For the four-ball test with all of the balls the same size, the Hertzian formula could be simplified as follows: where N is the positive pressure on the contact friction surface under the four-ball test, μ is the friction factor of the ball friction surface, R is the radius of the balls, and E is 2.085 × 10 5 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By calculating the Hertzian contact diameters, 34 we could get the friction state. For the four-ball test with all of the balls the same size, the Hertzian formula could be simplified as follows: where N is the positive pressure on the contact friction surface under the four-ball test, μ is the friction factor of the ball friction surface, R is the radius of the balls, and E is 2.085 × 10 5 .…”
Section: Resultsmentioning
confidence: 99%
“…3(c). By calculating the Hertzian contact diameters, 34 we could get the friction state. For the four-ball test with all of the balls the same size, the Hertzian formula could be simplied as follows:…”
Section: Tribological Properties Of Greasementioning
confidence: 99%
“…While several works have examined the tribologically induced wear of hydrogels that can serve as biological replacement materials [19,[86][87][88], the understanding of the mechanisms underlying tribologically promoted wear is not only lacking, but even more, the correlation is debated. Here, it is worth mentioning the work by Bonyadi et al [89], who performed systematic measurements to correlate wear, friction and surface stiffness of polyacrylamide hydrogels. The study revealed a temporary stiffening of the surface layer upon wear, which undergoes osmotic re-swelling, regains the pristine surface stiffness and corresponding low friction.…”
Section: Closing Remarks and Future Perspectivesmentioning
confidence: 99%
“…6). In the same line as the early discovery, recent work demonstrates a swollen outer layer on polyacrylamide that can be worn away, but re-emerges over time [87]. Authors hypothesized that a swollen surface region will always emerge due to the way that the solvated chains reconfigure to maximize the exclusion of water shells.…”
Section: Mold Materials and Imparted Propertiesmentioning
confidence: 84%
“…Particle exclusion microscopy (PEM) uses either fluorescent or dye particles to act as the primary signal within either the hydrogel itself or within the fluid surrounding the interface; where these particles are absent, the hydrogel must occupy [114]. By mounting a pin-on-disk micro-tribometer in the direct light path of an inverted microscope, PEM has been used to assess the contact mechanics of hydrogels as both probe and counter surface from the indirect observation of the contact area in both static indentation and dynamic sliding [115][116][117][118][119]. Similarly, direct measurements of contact area may also be accomplished with a micro-tribometer and fluorescence confocal microscope by three-dimensional reconstruction of the indented surfaces and probes by adding a small amount of dispersed nano-sized fluorescent particles to the hydrogel samples before polymerization [18,20,118].…”
Section: Updated Testing Techniquesmentioning
confidence: 99%